An Investigation of the Dravidian Model’s Claim to Superior Socioeconomic Development - Ramprakash, K. R.; Kunal, Kishore; Joe Arun, C. (Prabandhan: Indian Journal of Management, 2024)
Purpose : This investigation scrutinized the efficacy of the Dravidian model in socio-economic development within Tamil Nadu and juxtaposed it with the paradigms observed in Maharashtra and Gujarat to discern its impact on societal advancement. Methodology : The study examined several social and economic variables in these states using a longitudinal analysis spanning from 1991 to 2021. A thorough structural model was built to carefully investigate the relationship between the economic policies that were put into place and the social development indicators that emerged. Findings : The empirical data obtained from this research demonstrated a strong positive correlation between the Dravidian model’s application and Tamil Nadu’s social advancement, indicating the model’s greater effectiveness in comparison to Maharashtra and Gujarat states. This finding further demonstrated the Dravidian Model’s ability to accelerate socioeconomic development. Practical Implications : The results suggested that inclusive growth frameworks, which are similar to the Dravidian model, should be used as practical means of achieving long-term socioeconomic development. Policymakers and industry stakeholders’ strategic conversations will be informed and enhanced by this inference. Originality : This study departed from other investigations by providing empirical evidence that supports the Dravidian model’s pivotal function in promoting inclusive growth. As such, it contributed to the conversation about socioeconomic development tactics in developing nations.